Phototransformation of a Six Membered Ring Formyl Ketone (2-Formyl-1-tetralone) - Garg, S.; Kohli, J.C. (Asian Journal of Chemistry, 2010)
With a view to examine the structural dependence of photochemical change in β-dicarbonyl compounds irradiation of six membered ring formyl ketone i.e. 2-formyl-1-tetralone (I) was done in dry ethanol and benzene separately. This diketone was converted into 1-hydroxy-2-naphthaldehyde (II) in each case.